Perception of first respiratory infection with Pseudomonas aeruginosa by people with cystic fibrosis and those close to them: an online qualitative study - Palser, Sally C.; Rayner, Oliver C.; Leighton, Paul; Smyth, Alan R. (BMJ Publishing Group Ltd, 2016)
Background: People with cystic fibrosis (CF) are susceptible to respiratory infection with Pseudomonas aeruginosa (PA), which may become chronic if initial eradication fails. Environmental acquisition and person-to-person transmission can occur. Respiratory PA infection is associated with increased mortality and more hospitalisations. This may cause patients and families anxiety and lead them to adopt preventive measures which may be ineffectual and intrusive. It is not possible to hold a conventional focus group to explore these issues because people with CF cannot meet together due to the risk of cross-infection. Objective: To explore the perceptions of first respiratory infection with PA in people with CF and those close to them. Design: We designed an online survey, to maximise accessibility and avoid the risk of cross-infection. This established the respondent's relationship with CF, asked 3 open questions about perceptions of PA and a final question about the prioritisation of research. Responses were analysed using a structured, iterative process. We identified keywords, analysed these incontext and derived key themes. Setting: Promotion through social media allowed respondents from any country to participate. Participants: People with CF and those close to them. Results: Responses were received from 393 people, including 266 parents and 97 people with CF. The key themes were the emotional burden of PA (fear in particular); the burden of treatment PA entails and the need for accurate knowledge about PA. Conclusions: Lack of knowledge and the health beliefs of individuals may promote fear of infection and inappropriate avoidance measures. Uncertainty about the implications of PA infection and the treatment required may cause anxiety. Healthcare professionals should provide clear information about how PA might be acquired and the treatment necessary, making clear the limitations of current understanding and acknowledging health beliefs.